Ketika Koneksi Tidak Terputus: Sebuah Kasus Perilaku yang Tampak pada Orang Dewasa dengan Kecanduan Internet - Handy Wiranto; Felix Handani (Jurnal Sains dan Ilmu Terapan, 2025)
Internet addiction is a type of behavioral addiction marked by excessive and uncontrollable use of the internet, which adversely affects an individual's psychological and social well-being. This research investigates the psychological aspects of internet addiction among young adults in digital work environments, utilizing Pavlov's classical conditioning theory to explain the addictive behaviors. A qualitative case study approach was employed, involving a 26-year-old female participant who was evaluated through interviews, observations, and five psychological assessments: the Internet Addiction Test (IAT), DSM-5 criteria, the ABC model, the SORC model, and a self-recording diary. Findings revealed that the participant spent 15-20 hours online daily, primarily to escape stress and boredom, achieving an IAT score of 78, indicating severe addiction, and fulfilling over five DSM-5 criteria for behavioral addiction disorder. The analysis indicated that digital stimuli, such as notifications and visual cues, elicited compulsive responses, reinforcing automatic behaviors. The results align with Pavlov's theory, highlighting the importance of behavior-focused interventions, digital literacy, and social support in combating internet addiction among young adults.